Time interval between the completion of radiotherapy and robotic-assisted surgery among patients with stage I–III rectal cancer undergoing preoperative chemoradiotherapy - Huang, Ching-Wen; Su, Wei-Chih; Yin, Tzu-Chieh; Chen, Po-Jung; Chang, Tsung-Kun; Chen, Yen-Cheng; Li, Ching-Chun; Hsieh, Yi-Chien; Tsai, Hsiang-Lin; Wang, Jaw-Yuan (PloS one, 2020)
This aim of this study was to evaluate the effects of time interval between the completion of radiotherapy and robotic-assisted surgery on the outcomes among patients with rectal cancer undergoing preoperative concurrent chemoradiotherapy (CCRT). In total, 116 patients with stage I-III rectal cancer who underwent preoperative CCRT and robotic-assisted surgery between September 2013 and February 2019 were enrolled. Patients were categorized into two groups based on the time interval: group A (10-12 weeks) and group B (≥ 12 weeks). Among the 116 enrolled patients, 98 (84.5%) had middle and lower rectal cancers. Two (1.7%) patients underwent abdominoperineal resection with a sphincter preservation rate of 98.3%. Thirty-seven (31.9%) patients had a pathologic complete response (pCR). The circumferential resection margin and distal resection margin were positive in 2 (1.7%) and 1 (0.9%) patients, respectively. Therefore, the R0 resection rate was 97.4%. A total of 24 (22.4%) patients experienced postoperative relapse and 12 (10.3%) patients died; these were slightly more common in group B than in group A (28.8% vs 15.8% and 15.3% vs 5.3%, respectively; both P > 0.05); however, this difference was nonsignificant. Three-year disease-free survival (DFS) and overall survival (OS) were 75% and 89%, respectively, among all patients. Non-significant trend of favorable 3-year DFS, 3-year OS, 3-year locoregional control rate and 3-year distant metastasis control rate were observed in group A compared with group B (all P > 0.05). Robotic-assisted surgery after a longer interval is safe and feasible for patients with rectal cancer undergoing preoperative CCRT. The present study's results suggested that the time interval of 10-12 weeks can be considered because comparable clinical and perioperative outcomes and preferable oncological outcomes were observed for interval of this length. However, future prospective randomized clinical trials are required to verify the present finding.